Integrating Technology in Early Childhood Education: Opportunities and Challenges in Thailand - Miss Fatihah Saman (Yayasan pendidikan dzurriyatul Quran, 2025)
Early childhood education (ECE) plays a critical role in shaping children’s cognitive, social, and emotional development in the digital era. This study aims to analyze the opportunities and challenges of integrating technology into early childhood education in Thailand by examining national policies, teacher preparedness, and community engagement. Employing a qualitative descriptive approach, this research applies a systematic literature review of policy frameworks, UNESCO reports, and high-impact scholarly articles published within the last decade (2015–2025). The findings reveal that technology integration provides significant opportunities to enhance learning quality, personalize instruction, and expand access to education. However, challenges persist, including infrastructure disparities, limited digital literacy among teachers, insufficient culturally relevant content, and low parental involvement. The study highlights the need for collaborative strategies among policymakers, educators, parents, and technology developers to build an inclusive, sustainable, and child-centered learning ecosystem.